IMPACT OF DISASTERS ON DISASTER MEDICINE EDUCATION - Elena Valkanova; Rostislav Kostadinov (Peytchinski Publishing, 2021)
Introduction: Disaster medicine is a novel but rapidly evolving medical specialty. It aims for evidence based practices as they are essential for contemporary medicine. Every calamity provides input for development. Researchers in the field study these events for the purpose of amending theory and practice to reflect new challenges. The better the understanding of the shortfalls reported is, the greater will the worth for disaster medical response to the upcoming events be. Purpose: The objective of the study is to demonstrate the connection between disasters and commencement and evolution in disaster medicine education and to highlight the significance of lessons learned for practice improvement. Materials and methods: By means of the descriptive method, lessons learned from disaster medical support to some of the most significant catastrophic events in recent years are presented. Comparative and deductive analyses are performed in order to assess the influence of disasters on the evolution of disaster medical support education and training. Results: Analysis of the most consequential disasters proves that the affected countries have implemented disaster medical support planning, organization, and management changes. These changes in policy and practice lead to amendments and advances in disaster medical tuition. Conclusion: As a conclusion, disaster medicine education reliance on the best practices approved throughout the disaster relief operations is noted. Every gained experience and lesson learned have to be implemented into the lectures and seminars, thus transforming real life achievements into knowledge and wisdom.